A simple novel technique for closure of simple and complex pilonidal sinus with either simple (tongue-shaped) or bilobed rotation flap - Awad Mohamed; Saad Khaled; Tolba Adel; Gharib Osama (Indian Journal of Plastic Surgery)
Background: Pilonidal sinus is a common disease in young adults that carries high postoperative morbidity and patients′ discomfort; controversy still exists regarding the best surgical technique for the treatment of the disease. We successfully treat it with a rotation flap technique (simple rotation and bilobed rotation flap). Materials and Methods: Sixty-two patients were randomized to receive surgical treatment in the form of either simple rotation or bilobed rotation flap by eccentric elliptical excision of the diseased tissues down to the sacral fascia and closure of the defect with the flap, then placing a closed suction drain at the base of the wound, with its tip being brought out in the gluteal region at least 5 cm laterally to the lower end of the suture. Results: All our patients healed completely without recurrence after a mean follow-up of about one year. Mean hospital stay 1.5 days (range 1-3) Mean time to complete healing 11.9 days (range 8-14). Mean time off work was 11.5 days (range 10-21), wound infection and breakdown, three (4.8%), recurrence (0%), and time to sitting on the toilet and walking without pain was 10-15 days. Conclusions: A tension-free suture and cleft left via the rotation flap, either the bilobed flap or monolobed, is the key to success without recurrence and low patient discomfort.